Proceedings of the 17th International Middleware Conference 2016
DOI: 10.1145/2988336.2988346
|View full text |Cite
|
Sign up to set email alerts
|

Secure Content-Based Routing Using Intel Software Guard Extensions

Abstract: Content-based routing (CBR) is a powerful model that supports scalable asynchronous communication among large sets of geographically distributed nodes. Yet, preserving privacy represents a major limitation for the wide adoption of CBR, notably when the routers are located in public clouds. Indeed, a CBR router must see the content of the messages sent by data producers, as well as the filters (or subscriptions) registered by data consumers. This represents a major deterrent for companies for which data is a ke… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 30 publications
0
47
0
Order By: Relevance
“…The main sources of overhead for SGX enclaved executions are the transitions between protected and unprotected modes, and memory usage [18], [46]- [48]. Additionally, startup time is longer than traditional executions, mainly due to support service initialization and memory allocation.…”
Section: Evaluation Of Sgx Performancementioning
confidence: 99%
“…The main sources of overhead for SGX enclaved executions are the transitions between protected and unprotected modes, and memory usage [18], [46]- [48]. Additionally, startup time is longer than traditional executions, mainly due to support service initialization and memory allocation.…”
Section: Evaluation Of Sgx Performancementioning
confidence: 99%
“…Intel SGX is used to implement a Secure Content-Based Routing (SCBR) system [6], providing privacy preserving to messages, since they are not exposed to unauthorized parties and they are filtered only in a secure enclave. Extensive experiments concluded that SGX adds a limited overhead providing much better performance when compared to other alternatives of Secure CBR.…”
Section: Related Workmentioning
confidence: 99%
“…To avoid such kind of attacks, the data can be encrypted in the producers in order to be processed only in a secure way. This can be achieved by homomorphic cryptography [5], which performs common operations over encrypted data, but its great overhead makes it unpractical to use with complex operations [6]. Another approach is the use of a trusted execution environment (TEE), that enables, by using specific hardware instructions, the creation of a shielded space in the memory in a way data can be processed securely inside this space.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there is only one existing system (SCBR [26]) that efficiently combines the publish/subscribe paradigm with Intel SGX. SCBR integrates with Intel SGX by running the code of the brokers inside the enclaves, thus preventing an attacker with full control to inspect the messages in transit through the network.…”
Section: ) Pypy and Shielding Overheadmentioning
confidence: 99%